2019
DOI: 10.3390/app9020318
|View full text |Cite
|
Sign up to set email alerts
|

The Characterisation and Quantification of Immobilised Concanavalin A on Quartz Surfaces Based on The Competitive Binding to Glucose and Fluorescent Labelled Dextran

Abstract: The competition between various carbohydrates in the binding to Concanavalin A (Con A) can be exploited in gravimetric microsensors that detect changes in mass or viscoelasticity as a function of glucose concentration. Such sensors are based on the immobilisation of Con A as the ligand specific element, and a successful application requires that the binding property of Con A is retained. This paper presents a simplified immobilisation procedure of Con A on a quartz surface, a common material for gravimetric mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…After introduction of Con A, the aldehyde absorption peaks disappear (SI Figure S2). Due to the active group of Con A is amine group, 45 the disappearance of aldehyde absorption peaks indicates amine groups in Con A interacted with aldehyde in GA, and Con A has been favorably immobilized on PAA. Meanwhile, confocal Raman microscopy also shows the typical vibrations of different groups in Con A attached to PAA surface, including phenylalanine ring breathing mode (1003 cm −1 ) and various backbone amide bands (1233 cm −1 , 1556 cm −1 , 1670 cm −1 ) (SI Figure S3).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…After introduction of Con A, the aldehyde absorption peaks disappear (SI Figure S2). Due to the active group of Con A is amine group, 45 the disappearance of aldehyde absorption peaks indicates amine groups in Con A interacted with aldehyde in GA, and Con A has been favorably immobilized on PAA. Meanwhile, confocal Raman microscopy also shows the typical vibrations of different groups in Con A attached to PAA surface, including phenylalanine ring breathing mode (1003 cm −1 ) and various backbone amide bands (1233 cm −1 , 1556 cm −1 , 1670 cm −1 ) (SI Figure S3).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Before doing this, the detection time was optimized. As seen in Figure 5A, when cell solution is incubated with PAA for different time (5,10,20,30,45, 60, 90 min) at 37 °C, the I−V properties change continuously and then reach stable at ∼45 min. The captured cells could efficiently cover the outer surface of PAA, and impede the ionic flow through PAA, which results in a decreased current response.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…In this case, there is less chance that random molecular orientation of the lectin molecule on the substrate will result in a reduced number of functional binding sites. In addition, Hoang et al demonstrated by binding capacity of dextran to Con A covalently attached to a quartz surface that the density of active immobilized Con A was about 1/3 of the theoretical maximum surface coverage estimate. Previous studies suggest that adsorption to hydrophobic surfaces does not drastically reduce lectin sugar binding capacity, and that 15 min lectin deposition time is sufficient to obtain homogeneously covered substrates. , Both approaches result in the formation of lectin layers of different organization.…”
Section: Discussionmentioning
confidence: 99%
“…In the article on The Characterisation and Quantification of Immobilised Concanavalin A on Quartz Surfaces Based on The Competitive Binding to Glucose and Fluorescent Labelled Dextran [13] authored by T. Bich Hoang and coworkers, a simple protocol for the immobilization of Concanavalin A (Con A) on a quartz substrate, a common material for gravimetric microsensors, was developed. The binding activity of the immobilized Con A was assessed by measuring the intensity from fluorescent labelled dextran (FITC and Alexa 488; with a surface coverage ranging from 1.8 × 10 11 to 2.1 × 10 12 immobilized fluorescent molecules per cm 2 ) over a glucose concentration range from 0 to 40 mM, whereas any structural changes to the surface topography were investigated using AFM.…”
Section: Protein and Peptide Nanobiosensors For The Early Diagnosis Omentioning
confidence: 99%